2014
DOI: 10.1111/cogs.12185
|View full text |Cite
|
Sign up to set email alerts
|

State‐Trace Analysis: Dissociable Processes in a Connectionist Network?

Abstract: Some argue the common practice of inferring multiple processes or systems from a dissociation is flawed (Dunn, 2003). One proposed solution is state-trace analysis (Bamber, 1979), which involves plotting, across two or more conditions of interest, performance measured by either two dependent variables, or two conditions of the same dependent measure. The resulting analysis is considered to provide evidence that either (a) a single process underlies performance (one function is produced) or (b) there is evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Furthermore, Dunn et al. 's conclusions were strengthened using state‐trace analysis (Bamber, ; Loftus, Oberg, & Dillon, ), which failed to find evidence of two independent systems (although see Ashby, ; Dunn, Kalish, & Newell, ; Yeates, Wills, Jones, & Mclaren, , for a discussion of the limitations of this analysis).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, Dunn et al. 's conclusions were strengthened using state‐trace analysis (Bamber, ; Loftus, Oberg, & Dillon, ), which failed to find evidence of two independent systems (although see Ashby, ; Dunn, Kalish, & Newell, ; Yeates, Wills, Jones, & Mclaren, , for a discussion of the limitations of this analysis).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, the effect of reducing feedback time was found to dissociate between these two categorization tasks (Maddox, Ashby, Ing, & Pickering, 2004), but when the tasks were equated for perceptual difficulty the dissociation disappeared (Stanton & Nosofsky, 2007). Furthermore, Dunn et al's conclusions were strengthened using state-trace analysis (Bamber, 1979;Loftus, Oberg, & Dillon, 2004), which failed to find evidence of two independent systems (although see Ashby, 2014;Dunn, Kalish, & Newell, 2014;Yeates, Wills, Jones, & Mclaren, 2015, for a discussion of the limitations of this analysis). Furthermore, Dunn et al's conclusions were strengthened using state-trace analysis (Bamber, 1979;Loftus, Oberg, & Dillon, 2004), which failed to find evidence of two independent systems (although see Ashby, 2014;Dunn, Kalish, & Newell, 2014;Yeates, Wills, Jones, & Mclaren, 2015, for a discussion of the limitations of this analysis).…”
Section: Implications For Covismentioning
confidence: 99%
See 1 more Smart Citation
“…We think the answer to this question is yes and that the strongest evidence for this position comes from a novel use of the state-trace methodology introduced by Bamber (1979) and further developed by ourselves (Yeates, Wills, Jones, & McLaren, 2015). Figure 7 plots the median RT performance (we get similar results for errors) on each block for the incongruent stimuli that form the bi-conditional discrimination against the median performance for the same block on the congruent stimuli that comprise the simple discrimination.…”
Section: Resultsmentioning
confidence: 99%
“…For example, if damage to a particular brain structure led to deficits in performing task A but not task B (or even better, if damage to brain structure 1 led to deficits in performing task A but not task B, while damage to brain structure 2 led to deficits in performing task B but not task A), then functionally distinct mental and neural systems could be identified. Among many lines of evidence speaking against this strong form of inference (e.g., Kinder & Shanks, 2003; Munakata, 2001; Plaut, 1995), developments in state-trace analysis (Newell & Dunn, 2008; Stephens et al, 2019; Yeates et al, 2015) showed that dissociation patterns are rarely inconsistent with explanations based on a single latent construct that has monotonic but distinct mappings onto the measured dependent variables. For this reason, as well as the finding that many classic examples in the implicit/explicit domain have proven hard to replicate (e.g., Berry et al, 2014; Berry et al, 2017; Le Pelley et al, 2019; Ward et al, 2020; Zaki et al, 2003), dissociation logic has largely been abandoned in recent years.…”
Section: Theoretical and Conceptual Contextmentioning
confidence: 99%